Anisotropic phonon and magnon vibration and gate-tunable optoelectronic properties of nickel thiophosphite. (1st April 2023) - Muhammad, Zahir; Szpakowski, Jan; Abbas, Ghulam; Zu, Lin; Islam, Rajibul; Wang, Yan; Wali, Faiz; Karmakar, Arka; Molas, Maciej R; Zhang, Yue; Zhu, Ling; Zhao, Weisheng; et al.
Abstract: Transition metal phosphorus trichalcogenides retain spin-charge coupling and lattice vibrations in different layers, which are useful for spintronic and optoelectronic devices. The phonon, magnons and excitonic properties of two-dimensional ternary nickel-phosphorus trisulfides (NiPS3 ) are investigated using Raman spectroscopy and photoluminescence (PL) study. With magnetic exchange interaction, an exotic phonon scattering degenerates the optical phonons into in-plane A g and B g modes. We have observed eight Raman modes with two acoustic anisotropic magnon modes ( M 1, M 2 ) below the critical temperature for co-( XX ), while only M 1 at cross ( XY ) polarizations. The M 1 mode is coupled with the phonon B g mode that can survive after transition temperature. The phonon and magnon modes soften with variations in temperature, which is attributed to anharmonic phonon–phonon coupling and interlayer forces. The polarized Raman shows the two-fold and four-fold symmetry orientations of the phonon and magnon modes, respectively, which exhibit strong in-plane anisotropic phonon/magnon. The PL spectra revealed the existence of bound excitonic features and ensemble emitters in NiPS3 . The robust interlayer excitation and structural stability further revealed the optothermal properties. Moreover, the fabricated field-effect transistor on NiPS3 reveals p -type semiconducting nature with an ON/OFF ratio of 5 × 10 6 and mobility of ∼16.34 cm 2 V −1 s −1 . In contrast, the rectification ratio indicates their diode characteristics. Similarly, the photocurrent is enhanced by changing the wavelength of light, which shows the potential for optoelectronics. The strong spin-charge interaction provides new insights into these materials' magneto-optical and thermal properties for memory devices.